A co-evolutionary landscape ecology framework for analyzing human effects on KwaZulu-Natal Province landscapes and its relevance to sustainable biodiversity conservation - Van Jaarsveld, A.S. (University of Pretoria, 2013)
Thesis (DPhil (Sustainable Ecological Management))--University of Pretoria, 2007.